Video-Based Interventions for Cancer Control: A Systematic Review. (April 2020) - Blake, Kelly D.; Thai, Chan; Falisi, Angela; Chou, Wen-Ying Sylvia; Oh, April; Jackson, Devlon; Gaysynsky, Anna; Hesse, Bradford W.
Background. The use of videos for patient and public health education has been widely adopted and well documented in the literature. Aims. To conduct a systematic review of empirical studies that used video-based interventions for cancer prevention and control to document study designs, settings, approaches, targeted cancer sites and behaviors, and outcomes and to identify gaps in research and practice. Method. PubMed, PsychINFO, CINAHL, SCOPUS, and Web of Science were searched for studies published in the 30-year period from 1984 to 2014. Of 1, 521 articles identified, duplicates were removed, and titles and abstracts of 779 were examined for eligibility. In all, 315 articles met the inclusion criteria and were coded by three independent coders. Interrater reliability was assessed. Descriptive frequencies and proportions were calculated. Results. Studies evaluating video interventions for cancer prevention and control have increased over time. The majority used randomized controlled trial designs (54%), followed by single-group pre–posttest designs (18%). Most were delivered in health care settings (39%). Detection (30%) and treatment (16%) were the cancer control continuum stages most frequently addressed, with breast cancer (29%) being the most frequently targeted cancer site. The behavior most commonly targeted was screening/early detection (39%). Topics such as caregiving, coping, palliative care, and end of life were rarely addressed. The majority (69%) reported being successful at achieving their stated objectives, though outcomes varied across studies. Conclusions. Video interventions have been widely utilized for cancer prevention and control, with demonstrated successes. Future research should test innovative designs and new delivery platforms and should include underrepresented topics and cancer sites.